RELATIONSHIP OF CAREER SUCCESS AND ORGANIZATIONAL PERFORMANCE THROUGH THE PATH OF BUSINESS STRATEGY - Abdul Khaliq, Alvi; Zahra, Jabeen; Arif, Jawaid; Parveen, Kaur (The International Islamic University Malaysia, 2020)
Aim of this research was to find out the mediation of career success between the relationship of Business Strategy along with its four dimensions (Business Strategy prospectors,Business Strategy defenders, Business Strategy analyzers and Business Strategy reactors) and organizational performance. This research was conducted in the banking sector of Lahore, Pakistan. Data were collected through structured questionnaires by simple random sampling technique. Total 385 questionnaires were administrated to respondents;334 were returned,31were discarded and 303 were used for analysis. Findings showed significant impacts of Business Strategy on career success and organizational performance and for impact of these two kinds (Business Strategy Prospectors and Business Strategy Defenders) on organizational performance. The impact of two other factors (Business Strategy Analyzers and Business Strategy Reactors) on organizational performance was insignificant. Career success has positive significant effect on organizational performance. Career success partially mediates with Business Strategy(with its two kinds Business Strategy Prospector and Business Strategy Defender)with organizational performance. Business Strategy Analyzers and Business Strategy Reactors were rejected as mediators.Because of time constraint,data were not collected from more banks.This research adds to the body of literature by considering the mediation effect of career success between the relationship of Business Strategy as a whole and with dimensions of organizational performance,also by empirical checking of the relationship between career success and Business Strategy.